2017
DOI: 10.1038/s41467-017-02402-6
|View full text |Cite
|
Sign up to set email alerts
|

The podoplanin-CLEC-2 axis inhibits inflammation in sepsis

Abstract: Platelets play a critical role in vascular inflammation through the podoplanin and collagen/fibrin receptors, C-type-lectin-like-2 (CLEC-2) and glycoprotein VI (GPVI), respectively. Both receptors regulate endothelial permeability and prevent peri-vascular bleeding in inflammation. Here we show that platelet-specific deletion of CLEC-2 but not GPVI leads to enhanced systemic inflammation and accelerated organ injury in two mouse models of sepsis–intra-peritoneal lipopolysaccharide and cecal ligation and punctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 54 publications
4
134
0
1
Order By: Relevance
“…In this model, deletion of platelet‐CLEC‐2 resulted in an increased severity of sepsis that was associated with a dysregulation of inflammatory cytokine production, thus indicating a protective role of platelet CLEC‐2 . These findings showing a protective role of platelet CLEC‐2 in inflammation have since been published and are in line with those of a recent study demonstrating that platelet CLEC‐2 protects against LPS‐induced lung injury via its interaction with podoplanin on inflammatory alveolar macrophages . While it was previously shown that engagement of platelet CLEC‐2 by podoplanin on inflammatory macrophages triggers platelet activation, these new data indicate that this interaction induces reciprocal regulation between platelets and inflammatory macrophages.…”
Section: Isth Berlin Reportsupporting
confidence: 89%
See 1 more Smart Citation
“…In this model, deletion of platelet‐CLEC‐2 resulted in an increased severity of sepsis that was associated with a dysregulation of inflammatory cytokine production, thus indicating a protective role of platelet CLEC‐2 . These findings showing a protective role of platelet CLEC‐2 in inflammation have since been published and are in line with those of a recent study demonstrating that platelet CLEC‐2 protects against LPS‐induced lung injury via its interaction with podoplanin on inflammatory alveolar macrophages . While it was previously shown that engagement of platelet CLEC‐2 by podoplanin on inflammatory macrophages triggers platelet activation, these new data indicate that this interaction induces reciprocal regulation between platelets and inflammatory macrophages.…”
Section: Isth Berlin Reportsupporting
confidence: 89%
“…Those situations likely encompass most traumatic vascular injuries, which might explain why GPVI patients do not present severe bleeding. Indeed, besides lymphatic endothelial cells, several types of podoplanin‐expressing cells (inflammatory macrophages, fibroblasts) have been described in the vicinity of blood vessels and could therefore engage platelet CLEC‐2 through vascular breaches.…”
Section: Gpvi In Primary Hemostasis and Thrombosismentioning
confidence: 99%
“…Thus, podoplanin‐CLEC‐2 interaction clearly drove platelet activation, aggregation, and reduction in count in blood in vitro. However, here, and to a lesser extent in other recent studies in our facility , the responses to podoplanin ligation in the Clec1bfl/fl PFcre model of CLEC2 reduction were variable in vivo. We checked expression of CLEC‐2 on platelets, and found less than 5% of platelets from Clec1bfl/fl PFcre mice to be positively labeled by antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive Interactions of MSC in Flowing Blood V C 2018 The Authors STEM CELLS published by Wiley Periodicals, Inc. on behalf of AlphaMed Press STEM CELLS our facility [35], the responses to podoplanin ligation in the Clec1bfl/fl PFcre model of CLEC2 reduction were variable in vivo. We checked expression of CLEC-2 on platelets, and found less than 5% of platelets from Clec1bfl/fl PFcre mice to be positively labeled by antibody.…”
mentioning
confidence: 96%
“…Deletion of CLEC‐2 from platelets or PDPN from macrophages potentiates the cytokine storm and reduces PDPN expressing inflammatory macrophage migration to the infected peritoneum. In addition, pharmacological inhibition of the CLEC‐2‐PDPN axis inhibits immune cells infiltrate at the site of infection and regulates their inflammatory phenotype . These observations identify PDPN as a novel anti‐inflammatory target regulating immune cell recruitment and activation in sepsis.…”
Section: The Podoplanin Extracellular Domain As a Therapeutic Targetmentioning
confidence: 93%